KONSEP DIRI PENDERITA TB PARU DI RS PKU MUHAMMADIYAH GOMBONG - Rina Saraswati; Nur Hasanah; Muhammad Basirun Al Ummah (Jurnal Ilmiah Kesehatan Keperawatan, 2016)
Introduction: The self-concept is all thoughts, beliefs and faiths that make the person know about him and affect his contact with others. Usually self-concept of pulmonary tuberculosis patients is impaired resulting from physical changes such as becoming physically thinner, paler, frequent coughing, body weaknesses and decrease of physical ability. Based on preliminary studies on eight respondents 75% experiencing body image disorder, 75% self-ideal disorder, 100% self-role disorder, 50% self-esteem disorder.The aim of this researrch is to determine self-concept of pulmonary tuberculosis patients in PKU Muhammadiyah Hospital of Gombong.The present study used descriptive quantitative method with survey approach. The total samples were 31 people taken by purposive sampling technique. The data were taken by questionnaires and analyzed using univariate analysis.The frequency distribution based on the self-concept were less (83.9%), mediocre (9.7%), and good category (6.5%). The body image were less (83.9%), mediocre (9.7%), good (6.5%). The self-ideal were less (90.3%), and mediocre category (9.7%). Personal identity were less (58.1%), enough (22.6%), and good category (19.4%). The self-role were less (54.8%), good (25.8%), and mediocre category (19.4%). Self-esteem were less (51.6%), mediocre (32.3%), and good category (16.1%).The largest percentage of the self-concept, body image, self-ideal, personal identity, self-role, and self-esteem of pulmonary tuberculosis patients was less category. Keywords: self-concept, body image, self-ideal, personal identity, self-role, self-esteem, pulmonary tuberculosis patients